2008
DOI: 10.1371/journal.pone.0002013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Membrane Potential in Human Neutrophils Is Maintained by Complex III Activity in the Absence of Supercomplex Organisation

Abstract: BackgroundNeutrophils depend mainly on glycolysis for their energy provision. Their mitochondria maintain a membrane potential (Δψm), which is usually generated by the respiratory chain complexes. We investigated the source of Δψm in neutrophils, as compared to peripheral blood mononuclear leukocytes and HL-60 cells, and whether neutrophils can still utilise this Δψm for the generation of ATP.Methods and Principal FindingsIndividual activity of the oxidative phosphorylation complexes was significantly reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(157 citation statements)
references
References 36 publications
9
147
1
Order By: Relevance
“…Incubation with these agents alone did not induce NET formation and did not affect PMA-induced cell death kinetics (Supplementary information, Figure S3), which suggests that mitochondrial depolarization is not a crucial mediator of DNA decondensation. In this regard, it is noteworthy that neutrophils depend on glycolysis instead of oxidative phosphorylation to meet their energy demands [23,24]. This is in agreement with the profound decrease in the number of mitochondria during differentiation of precursor cells into neutrophils [25].…”
Section: Pma Induces Typical Features Of Netosis Which Differs Both supporting
confidence: 71%
See 1 more Smart Citation
“…Incubation with these agents alone did not induce NET formation and did not affect PMA-induced cell death kinetics (Supplementary information, Figure S3), which suggests that mitochondrial depolarization is not a crucial mediator of DNA decondensation. In this regard, it is noteworthy that neutrophils depend on glycolysis instead of oxidative phosphorylation to meet their energy demands [23,24]. This is in agreement with the profound decrease in the number of mitochondria during differentiation of precursor cells into neutrophils [25].…”
Section: Pma Induces Typical Features Of Netosis Which Differs Both supporting
confidence: 71%
“…To examine whether loss of mitochondrial membrane potential is sufficient to induce NETosis or possibly affects PMA-induced NETosis, we treated neutrophils with the protonophore carbonyl cyanide 3-chlorophenylhydrazone (CCCP) and the complex III inhibitor antimycin A. Both CCCP and antimycin A are known to dissipate the mitochondrial membrane potential in neutrophils [23]. Incubation with these agents alone did not induce NET formation and did not affect PMA-induced cell death kinetics (Supplementary information, Figure S3), which suggests that mitochondrial depolarization is not a crucial mediator of DNA decondensation.…”
Section: Pma Induces Typical Features Of Netosis Which Differs Both mentioning
confidence: 99%
“…1B), a proapoptotic protein whose content in neutrophils is very low [28]. Neutrophils contain relatively few mitochondria that maintain their inner mitochondrial membrane potential and play a role in the regulation of apoptosis [29]. Using flow cytometry, we observed that differentiation decreased the stainability of HL-60 cells with a mitochondria-specific dye TMRE (Fig.…”
Section: Differentiation Of Hl-60 Cells By Atra and Dmsomentioning
confidence: 87%
“…Neutrophilic differentiation is associated with changes in the abundance and function of mitochondria. Neutrophils contain few mitochondria which do not produce energy by respiration, but still maintain their ∆Ψ m and regulate the apoptotic processes [29,42]. Neutrophils also have a lowered requirement for cytochrome c for the engagement of the intrinsic pathway [28].…”
Section: Discussionmentioning
confidence: 99%
“…Cells of myeloid lineages derive their energy almost exclusively from glycolysis, whereas lymphocytes predominantly use oxidative phosphorylation [8,9]. [16].…”
Section: Interconnection Between Rosmentioning
confidence: 99%